The approach of Abu Bakr Al- " Faryabi (d. 301 AH) in the book Evidence of Prophet hood )Subject review article( - Dr. Naglaa Karim Mahdi (Genius Journals, 2023)
Abu Bakr Al-Faryabi is considered one of the most prominent historians of the Prophet’s biography in the second century AH, and it is not hidden from the reader the extent of the efforts he made during his scientific career. He was a trustworthy and trustworthy vessel of knowledge, and he wrote useful books. His book Evidence of Prophet hood was one of the most prominent books he wrote. It included supporting texts and divided it into two chapters. The first chapter included what was narrated that the Prophet, may God bless him and grant him peace, used to pray for a little food and place blessings in it until many people were satisfied with it. As for the second chapter, it was entitled “What was narrated that the Prophet used to pray or place “His hand is in some water, and much of creation is irrigated from it.” In it, Al-Faryabi presented the miracles and evidence of the prophecy of the Prophet of the Nation, Muhammad, may God bless him and grant him peace, which He, Glory be to Him, honored in him
Keywords: Al-Faryabi; curriculum; the honorable biography of the Prophet